2014
DOI: 10.1007/s10658-014-0451-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacterial isolates for biological control of clubroot on Chinese cabbage

Abstract: Clubroot caused by Plasmodiophora brassicae is becoming an emerging threat to the production of crucifer vegetable crops in China. The aim of this study was to develop an effective biocontrol strategy against clubroot of Chinese cabbage. Results indicated that six out of fourteen bacterial strains that were isolated from vegetable rhizosphere soil reduced disease severity of Chinese cabbage by more than 50.% under greenhouse conditions.In greenhouse experiments, a soil-drench application of strain YFY 02, 13-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Two potential biocontrol strains, F85 and T113 both exhibited good inhibitory effects on germination and viability of resting spores (Supplementary Figure S3), and produced greater than 80% disease suppression in greenhouse experiments. The efficacy of these two strains is better than that of previously reported biocontrol strains (Jäschke et al, 2010;Lahlali et al, 2013;Zhou et al, 2014). In order to improve the efficiency of the biocontrol agents under high disease pressure, it will be necessary to examine the combined effect of F85 and T113 against P. brassicae in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Two potential biocontrol strains, F85 and T113 both exhibited good inhibitory effects on germination and viability of resting spores (Supplementary Figure S3), and produced greater than 80% disease suppression in greenhouse experiments. The efficacy of these two strains is better than that of previously reported biocontrol strains (Jäschke et al, 2010;Lahlali et al, 2013;Zhou et al, 2014). In order to improve the efficiency of the biocontrol agents under high disease pressure, it will be necessary to examine the combined effect of F85 and T113 against P. brassicae in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two L. antibioticus strains also controlled the phytopathogenic protist Plasmodiophora brassicae , the causal agent of clubroot of crucifers (Table ; Zhou et al . ).…”
Section: Suppressive Soils and Biological Control Of Plant Diseasesmentioning
confidence: 97%
“…The L. antibioticus 13‐6 genome contains a cluster of genes deputed to the production of betalain pigments (Zhou et al . ), whereas the L. capsici AZ78 (Puopolo et al . ) genome encompasses genes involved in the biosynthesis of xanthomonadin‐like pigments sharing homology with genes first identified in L. enzymogenes OH11 (Wang et al .…”
Section: Understanding How Biocontrol Lysobacter Strains Interact Witmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Lysobacter represents a source of biocontrol agents, which consisted of 16 species ( 1 , 2 ). Recently, we reported that application of L. antibioticus 13-6 can control brassicae clubroot ( 3 ). Due to its tremendous potential application value, we analyzed the draft genome sequence of L. antibioticus 13-6.…”
Section: Genome Announcementmentioning
confidence: 99%